PENGARUH PERMAINAN ULAR TANGGA TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK DARUL JANNAH KABUPATEN KAMPAR - Wahyu Jumiarti; Jaspar Jas; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims 1) To determine the ability to recognize the concept bilangananak children aged 5-6 years at Tk Darul Jannah Kampar before giving the game of snakes and ladders. 2) To determine the ability to recognize the concept of numbers in children aged 5-6 years in kindergarten Darul Jannah Kampar regency after the game of snakes and ladders. 3) To determine how much influence the ability to know the concept of numbers in children aged 5-6 years in kindergarten Darul Jannah Kampar after giving the game of snakes and ladders. This type of research is an experimental research. The research sample is the child class B consisting of 20 children in kindergarten Darul Jannah Kampar with details of 10 boys and 10 girls .. The data was collected using observation and documentation. Based on the survey results revealed that 1) The ability to recognize the concept of numbers in children aged 5-6 years in kindergarten Darul Jannah Kampar before treatment is given in the form of a game of snakes and ladders are low. 2) The ability to recognize the concept of numbers in children aged 5-6 years in kindergarten Darul Jannah Kampar after treatment is given in the form of snakes and ladders game has increased and is high. 3) The game of snakes and ladders have a significant impact on the ability to know the concept of numbers in children aged 5-6 years in kindergarten Darul Jannah Kampar regency. It can be seen that there are differences in the form of increased ability to know the concept of numbers in children before and after treatment. 4) The game of snakes and ladders have an impact of 27.7% on the ability to know the concept of numbers in children aged 5-6 years in kindergarten Darul Jannah Kampar regency.Keywords : Snake and Ladder Game, Numbers Concept